External and Internal Economic Drivers of Financial Performance: Evidence from PT Pertamina - Mercy Nataly; Aris Soelistyo; Firdha Aksari Anindyntha (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2026)
This study aims to analyze the influence of external and internal factors on the financial performance of PT Pertamina (Persero) as measured using Return on Asset (ROA). External factors include world oil prices and inflation, while internal factors such as production expenses and total sales. The study used quarterly time series data for the period 2015Q1–2024Q4 with saturated sample technique and analyzed using multiple linear regression of the Ordinary Least Square (OLS) approach, which was preceded by stationariness tests, classical assumptions, and hypothesis testing. The results show that world oil prices and total sales have a significant positive effect on ROA, while inflation and production expenses have a significant negative effect. Simultaneously, all independent variables have a significant effect with a high power to explain the model. These findings confirm that the asset profitability of strategic energy companies is influenced by macroeconomic dynamics and operational efficiency simultaneously. However, the study was limited to the use of specific variables, static OLS approaches, and single objects. Further research is recommended to include additional macroeconomic and structural variables and use dynamic econometric methods or comparative approaches to strengthen the generalization of findings.